What to do when the earth shakes? DCH or door frames: evaluating generalised risk minimisation guidance - Sheena Ramkumar (Frontiers in Communication)
IntroductionWhat are the best, most effective protective action measures for people to take in a given context in order to minimise earthquake risks? Currently, experts and earthquake safety organisations offering risk minimisation communication do so in a generalised, one-size-fits-all approach, which can prove counterproductive. In this paper I address this question on the basis of research conducted in Nepal and Aotearoa/New Zealand.MethodsThis paper offers a critical discourse analysis of paradigm perspectives, knowledge apparatuses, narratives, and epistemic framings that dictate the trajectory of development and dissemination of Protective Action Measures (PAMs).ResultsDuring my field work in Nepal, I observed and heard through interviews and group discussions with several NGOs and organisations that during the 2015 Gorkha earthquakes, people were confused about what PAMs to take to minimise risks. Not only were people confused about what was the most suitable PAM to take during earthquakes, but were also perplexed about how to apply the guidance offered by organisations. Individuals and their families who tried to follow such guidance found that, as a result, they were faced with increased risks and the loss of more lives. Moreover, a Google Trends search revealed that in at least two major hazard events, people searched for outdated PAMs and advice, asking Google if this is what they should do.DiscussionRisk communication methods, PAMs and risk minimisation guidance require a closer critical examination and evaluation on a context-by-context basis, rather than the generalised messaging currently adopted. Risk minimisation guidance and PAMs that are not context sensitive have the potential for increasing and creating newer risks rather than effectively minimising existing risks.